Bringing Automatics and Robotics closer to pre-university students. Issue 17 (2022) - Hoyo, Á.; Mañas-Álvarez, F.J.; Rodríguez-Miranda, E.; Gil, J.D.; Castilla, M.; Guzmán, J.L.
Abstract: This article describes the experience of the Automatic Control, Robotics and Mecha-tronics Research Group from the University of Almería in the participation and preparation of workshops for teaching programming, control engineering and robotics to young students. All the activities designed to encourage the study of STEM careers among young students are described. Some activities are focused on directly promoting Automatics and Robotics disciplines. Others deal with encouraging the participation of women in science, and so, breaking gender inequality. Two main workshops, where first- and second-year students collaborate directly with the University of Almería, are also described in detail. Finally, this paper shows the growth in the number of students who enrolled in engineering degrees thanks to these dissemination activities.